Reclaiming the right to rice : food security and internal displacement in eastern Burma - Burmese Border Consortium (Thailand) (Bangkok Burmese Border Consortium, 2003)
This report aims to enhance awareness of human rights deprivations and the lack of food security which are a daily reality for internally displaced persons in eastern Burma. It was conceived as a forum in which community-based organisations could present their observations and participate in promoting their right to adequate food. The twelve contributing authors offer a range of local perspectives which combine to update and inform policy makers, relief and development practitioners, human rights defenders and the general public alike. -- From first paragraph of Introduction section.
Keywords: Right to food -- Burma. Food security -- Burma. Food supply -- Government policy -- Burma. Internally displaced persons -- Burma -- Social conditions. Food security. Food supply -- Government policy. Right to food. Burma